The ecological footprint of international tourists in New Zealand : a thesis presented in partial fulfilment for the degree of Master of Applied Science in Natural Resource Management at Massey University, Palmerston North, New Zealand - O'Connor, Katrina Marie (Massey University, 2009)
Ecological Footprint Analysis (EFA) is a technique that was first developed by Wackernagel as a Ph.D. thesis in 1994, then further developed in combination with Rees and published (Rees & Wackernagel, 1995). EFA is employed in this study to assess the resource utilisation of international tourists visiting New Zealand. Tourism is one of the fastest growing industries in the world and the ecological sustainability of tourism is becoming more important term for managing tourism. This is becoming increasingly important with tourism identified as particularly as a significant contributor to carbon emissions. This study uses EFA to assess whether international tourists visiting New Zealand behave in a sustainable manner. Tourists are surveyed and classed into high, mid and low budget tourist types to gain a detailed account of their behaviour with particular reference to food, accommodation, transport, services, activities attractions, goods and waste. The EFA helps to identify areas of a tourist’s trip that have the greatest impact on the environment, thereby identifying ways to improve the sustainability of tourism in New Zealand. It was found that tourists generally consume more whilst on holiday than they do at home and more than New Zealand residents. The results show that international tourists’ behaviour is sustainable and New Zealand has the ecological carrying capacity to allow the number of international tourists to increase without incurring any significant ecological costs to the country. It was found that there is a positive relationship between ‘high’ income tourists and their ecological footprint and that independent travellers have a larger ecological footprint than the package travellers; however, package travellers have a larger food and housing ecological footprint than independent travellers. The energy footprint was the largest out of the six land types of a tourist’s ecological footprint. Food is the consumption category that is the largest contributor to a tourist’s ecological footprint.
Keywords: Ecological footprint analysis; Tourism; Environmental impact; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300800 Environmental Science::300803 Natural resources management